Student Motivation to Participate in Corner Learning for Class X BDP 1 and 2 Students at SMK Negeri 9 Samarinda - Armain, Armain (PT Literasi Nusantara Publisher, 2022)
This research aims to determine the motivation of students to take part in PJOK learning at SMK Negeri 9 Samarinda. This research is a quantitative descriptive research with a survey method. The data collection technique in this research uses a questionnaire instrument. The population in this study were all class X BDP 1 dan 2 students at SMK Negeri 9 Samarinda using purposive sampling, with a total of 60 students. Data analysis uses descriptive analysis with percentages. Based on the overall research results of 60 students, of which in the